The use of organolithium reagents for the synthesis of 4-aryl-2-phenylpyridines and their corresponding iridium(iii) complexes. Issue 28 (27th June 2016) - Davidson, Ross; Hsu, Yu-Ting; Batchelor, Thomas; Yufit, Dmitry; Beeby, Andrew
Abstract : A versatile palladium-free route for the synthesis of 4-aryl-substituted phenylpyridines (ppy), starting from tert -butyl 4-oxopiperidine-1-carboxylate, to give 4 ligands (L 1–4 H) is reported. These ligands were coordinated to iridium to give the corresponding Ir(L)2 (A) complexes. Abstract : A versatile palladium-free route for the synthesis of 4-aryl-substituted phenylpyridines (ppy), starting from tert -butyl 4-oxopiperidine-1-carboxylate, is reported. Reaction with an aryllithium, followed by trifluoroacetic acid dehydration/deprotection and oxidation with 2-iodoylbenzoic acid and finally phenylation, gave 4 ligands (L 1–4 H): 2, 4-diphenylpyridine, 4-(4-methoxyphenyl)-2-phenylpyridine, 2-phenyl-4-( o -tolyl)pyridine and 4-mesityl-2-phenylpyridine. These ligands were coordinated to iridium to give the corresponding Ir(L)2 (A) complexes (Ir1–7 ), where A = ancillary ligand acetylacetate or 2-picolinate. This was used to demonstrate that, through a combination of ancillary ligand choice and torsional twisting between the 4-aryl substituents of the ppy ligands, it is possible to tune the phosphorescent emission of the complexes in the range 502–560 nm.